Mechanical Strength Analysis of Concrete with Partial Replacement of Fine Aggregates by Iron Slag and Cement by Silica Fume (International Journal of Innovative Research in Engineering & Management, 2022)
The world's population is becoming more  environmentally conscious, and as a result, regulations  governing the management of industrial waste are  becoming more stringent. As a result, the world's attention  is increasingly being directed toward researching the  properties of industrial waste and finding solutions on how  to make use of the waste's valuable component parts. This  is done in the expectation that these priceless component  components can be repurposed for use as secondary raw  material in one or more other types of industrial  applications. This report demonstrates that it is possible to  use iron slag as a partial replacement for sand and silica  fume as a partial replacement of cement in concrete. This is  accomplished by taking into account the specificity of the  physical and chemical properties of these products. In  addition, the report also takes into account the optimized  content of these two materials. An investigation into the  mechanical properties is provided. According to the  findings, the strength attributes of concrete significantly  improve when iron slag and silica fume are used to partially  substitute for sand and cement in the optimized  combination.
Keywords: Iron Slag; Silica Fume; Concrete; Strength; Environment